Death valley : [large type] a novel - Broder, Melissa (Thorndike Press large print high octane., 2024)
"In Melissa Broder's astounding new novel, a woman arrives alone at a Best Western seeking respite from an emptiness that plagues her. She has fled to the California high desert to escape a cloud of sorrow--for both her father in the ICU and a husband whose illness is worsening. What the motel provides, however, is not peace but a path, thanks to a receptionist who recommends a nearby hike. Out on the sun-scorched trail, the woman encounters a towering cactus whose size and shape mean it should not exist in California. Yet the cactus is there, with a gash through its side that beckons like a familiar door. So she enters it. What awaits her inside this mystical succulent sets her on a journey at once desolate and rich, hilarious and poignant"--